PEDULI COVID ’19 DIMULAI DARI ORANG DI SEKITAR KITA - Hapsari, RR. Prima Dita (UNIT PENGABDIAN KEPADA MASYARAKAT - UTPAS, 2023)
Humans are social creatures who certainly have to help each other, especially in the midst of a virus attack that has become the scourge of all humans in the world. There is no party, level or aspect that is not affected by Covid 19. Health workers are the main pillar needed to suppress and anticipate this war. This activity was held out of concern for the condition of the people affected by Covid. Working together, the team obtained donors who were willing to be part of organizing this activity. As a result, materials were collected that could be donated amid the soaring prices of these items. One thing is certain, the team feels concern about an outbreak will be the initial milestone in solving the problem.